Hemizygous nonsense variant in the moesin gene (MSN) leads to a new autoimmune phenotype of Immunodeficiency 50 - Kovács, András L.; Kárteszi, Judit; Prohászka, Zoltán; Kalmár, Tibor; Késmárky, Gábor; Koltai, Katalin; Nagy, Zsuzsanna; Sebők, Judit; Vas, Tibor; Molnár, Krisztián; Berki, Tímea; Böröcz, Katalin; et al. (Frontiers in Immunology, 2022)
Here we describe the investigation of two male siblings with juvenile total loss of teeth, early onset chronic leg ulcers and autoimmune thyroiditis in both patients, as well as focal segmental glomerulosclerosis with associated pulmonal emphysema in one and diabetes mellitus in the other patient. The clinical picture and lupus anticoagulant, cryoglobulin and cold agglutinin positivity suggested the diagnosis of antiphospholipid syndrome. Flow cytometry analysis showed immunophenotypes consistent with immune dysregulation: low number of naive T cells, elevated CD4+ T cell counts and decreased CD8+ T cell counts were detected, and more than half of the T helper population was activated. Because of the siblings’ almost identical clinical phenotype genetic alteration was suspected in the background of the immunodeficiency. Whole exome sequencing identified a previously not described hemizygous nonsense variant (c.650G>A, p.W217X) within exon 6 of the moesin gene (MSN) localized on chromosome X, resulting in significantly decreased MSN mRNA expression compared to healthy controls. We present a putative new autoimmune phenotype of Immunodeficiency 50 (MIM300988) characterized by antiphospholipid syndrome, Hashimoto’s thyroiditis, leg ulcer and juvenile loss of teeth, associated with W217X mutation of the MSN gene.